Fluoroalkyl-substituted fullerene/perovskite heterojunction for efficient and ambient stable perovskite solar cells. (December 2016) - Liu, Xiao; Lin, Francis; Chueh, Chu-Chen; Chen, Qi; Zhao, Ting; Liang, Po-Wei; Zhu, Zonglong; Sun, Ye; Jen, Alex K.-Y.
Abstract: In this paper, we investigate the feasibility of using a fluoroalkyl-substituted fullerene/perovskite heterojunction (f-FPHJ) to realize efficient and ambient stable perovskite solar cells (PVSCs). The hybrid fluoroalkyl-substituted fullerene, DF-C60, is proven to effectively passivate the defects and grain boundaries in the perovskite film to facilitate charge transport/collection in the derived PVSC. Consequently, the f-FPHJ device yielded an enhanced PCE of 18.11%, outperforming that of the pristine CH3 NH3 PbI3 device (15.67%). More interestingly, the f-FPHJ PVSC showed a decent PCE of 15.14% (under reverse scan) with small hysteresis even without employing a discrete PCBM electron-transporting layer (ETL), in contrast to the pristine PVSC showing a lower PCE of 14.78% (under reverse scan) accompanied with severe hysteresis. This might arise from the preferential distribution of DF-C60 nearby the surface region of the f-FPHJ film due to its low surface energy, which serves the similar function of the PCBM ETL in device to reduce hysteresis. More importantly, benefitting from the hydrophobic nature of DF-C60, the f-FPHJ PVSC shows respectable ambient stability without encapsulation, which can maintain 83% of its initial PCE after being stored in ambient (with a relative humidity of 60±5%) for 1 month. Graphical abstract: Fluoroalkyl-substituted fullerene/perovskite heterojunction (f-FPHJ) was developed in this study. The fluoroalkyl-substituted fullerene, DF-C60, not only can effectively passivate the defects/grain boundaries of perovskite but also increase its hydrophobicity. Consequently, a high power conversion efficiency (PCE) of 18.11% can be realized with respectable ambient stability. Interestingly, the f-FPHJ device can still deliver a decent PCE of 15.14% with small hysteresis even without employing a discrete PCBM electron-transporting layer (ETL), which might results from the preferential distribution of DF-C60 nearby the surface region of the f-FPHJ film to partially mimic the PCBM ETL to reduce the hysteresis. Highlights: We describe a fluoroalkyl-substituted fullerence/perovskite heterojunction (f-FPHJ) perovskite solar cell (PVSC) and realize an enhanced power conversion efficiency (PCE) from 15.67% (pristine of MAPbI3 PVSC) to 18.11%. The f-FPHJ PVSC can also deliver a decent PCE of 15.14% with small hysteresis even without employing a discrete PCBM electron-transporting layer (ETL), in contrast to the pristine PVSC showing a lower PCE of 14.78% accompanied with severe hysteresis. Benefitting from the hydrophobicity nature of DF-C60, the f-FPHJ PVSC shows a much enhanced ambient stability than the pristine CH3 NH3 PbI3 PVSC, which can maintain 83% of initial PCE after being stored in the ambient condition with a relative humidity of 60±5% for 1 month without encapsulation.